ANALISIS PENERAPAN TAX REVIEW ATAS PAJAK PENGHASILAN BADAN PADA HOTEL X TAHUN 2014 - Saridewi, Putu Ari Putri; Noviari, Naniek (E-Jurnal Akuntansi, 2017)
Tax review or review of tax is the act of a review of all transactions the company and should be carried out continuously to minimize errors that may occur, the review of tax can also be used to prepare a corporate plan ahead so that the efficiency of unnecessary costs can be minimized. The purpose of this study was conduct a review of the corporate income tax at the Hotel X. This research was conducted at the Hotel X. Hotel X is a company that engaged in the field of tourism. The method used in this study were interviews and documentation.The type of data that used in this research is qualitative form of organizational structure and quantitative data that used in this research is financial statements. Design of this research is quantitative descriptive. Based on the results of research that has been done. Hotel X has been running a deposit and reporting obligations in accordance legislation. However, in the calculation and Board Annual tax return preparation, there is an error that led to charges of tax payable in accordance with the applicable regulations. So that the necessary corrections to the charges.To avoid mistakes that may occur in the future, there’s recommended that the Hotel X must  apply this tax review every month as this will be very helpful in planning to estimated cost that will be used and before the tax government do any inspection Hotel X should immediately make a correction of all transactions that have not corrected yet. Keywords: Tax Review, Corporate Income Tax, Tax Liability, Tax Compliance
Keywords: Tax Review, Corporate Income Tax, Tax Liability, Tax Compliance